2000
DOI: 10.1074/jbc.m908162199
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of Caveolin Attenuates Epidermal Growth Factor Signaling in Senescent Cells

Abstract: Senescent human diploid fibroblasts do not respond to growth factors like epidermal growth factor (EGF), although they have a normal level of receptors and downstream signaling molecules. To examine the mechanism of signaling attenuation, we investigated Erk activation after EGF stimulation in senescent cells. Senescent cells did not phosphorylate Erk-1/2 after EGF stimulation, whereas young cells did. In those senescent cells, we found an increased level of caveolin proteins and strong interactions between ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
183
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(204 citation statements)
references
References 41 publications
21
183
0
Order By: Relevance
“…Senescent cells are resistant to mitogeninduced proliferation (Aggarwal et al, 1995;Park et al, 2000), express senescence-associated b-galactosidase (SAb-gal) (Dimri et al, 1995), have a characteristic enlarged, flattened morphology (Wagner et al, 2001), and show altered gene expression (Smith and Pereira-Smith, 1996). RNA differential displays and the serial assessment of gene expression (Welle et al, 2001) have been applied to explore senescence-associated genes to gain an insight into the molecular mechanisms underlying senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Senescent cells are resistant to mitogeninduced proliferation (Aggarwal et al, 1995;Park et al, 2000), express senescence-associated b-galactosidase (SAb-gal) (Dimri et al, 1995), have a characteristic enlarged, flattened morphology (Wagner et al, 2001), and show altered gene expression (Smith and Pereira-Smith, 1996). RNA differential displays and the serial assessment of gene expression (Welle et al, 2001) have been applied to explore senescence-associated genes to gain an insight into the molecular mechanisms underlying senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular senescence has also been characterized by increases in the levels of some senescence‐associated proteins, such as P‐ERK1/2 (Lim et al ., 2000), caveolin‐1 (Park et al ., 2000), and cell cycle regulators like p53, p16 ink4a , and p21 waf1 (Yeo et al ., 2000b). Therefore, to confirm PPKO‐induced cellular senescence, we examined levels of these proteins by Western blot analysis after treating HDFs with 1 mM PPKO for 3–7 days.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a close examination of the EM of caveolar structures ( Figure 6 of Bai's paper [6]), revealed that they are caveolar vesicles and not cave like structures at the membrane. These pinched off vesicles may represent a unique misregulation of caveolae in senescent cells that could explain both the functional differences and the increase in caveolar structures observed previously [7,8]. This misregulation may also explain why PTRF leads to DNA damage.…”
mentioning
confidence: 98%
“…The original investigations into the relationship between caveolae and senescence showed a unexpected upregulation of the proteins caveolin-1 and 2 during replicative senescence [7,8]. It was unclear what caused this upregulation, and now Bai et al demonstrated that it is due to the regulatory cavin protein, PTRF, which is known to drive the biogenesis of caveolae [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation